A Comparative Study of Self‐Assembled Superstructures from Cellulose Stearoyl Ester and Poly(Vinyl Stearate). Issue 18 (23rd August 2018) - Wang, Yonggui; Zhang, Chi; Tian, Jia; Xie, Yanjun; Zhang, Kai
Abstract: Comb‐like cellulose stearoyl ester (CSE3 ) and poly(vinyl stearate) (PVS) with distinct skeletons are successfully synthesized. Their self‐assembled superstructures are described and discussed comparatively herein. Differential scanning calorimetry investigation indicates that both comb‐like polymers with various molecular weights show the feasibility to form self‐assembled crystalline structures. The self‐assembled superstructures are obtained from both the evaporation‐induced and temperature‐induced phase separation processes. Due to the interference of different skeletons, self‐assembled superstructures of both comb‐like polymers demonstrate totally different morphologies. CSE3 with semi‐flexible skeleton forms robust petals, which further grows into well‐organized flower‐like particles. In contrast, PVS with more flexible skeleton only form non‐ordered porous structures through stacking of the wrinkled and folded nanofilms. Abstract : Various self‐assembled superstructures with distinct morphologies are obtained from two kinds of comb‐like polymers containing stearoyl side chains. Cellulose stearoyl ester and its fractions with semi‐flexible skeleton form well‐organized flower‐like particles, while poly(vinyl stearate) and its fractions with flexible skeleton only form porous structures stacked by the wrinkled and folded nanofilms.